1997
DOI: 10.1177/019791839703100406
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation and its Discontents: Between Rhetoric and Reality

Abstract: The process of immigrant assimilation is typically and uncritically conceived as one of linear progress -becoming similar to the dominant group in the place of destination is presumed to be a good thing. But a compelling body of evidence on the adaptation of immigrants and their children points to a deterioration of outcomes over time and generation in the United States, as well as to nonlinear processes of change. While linguistic assimilation among children of immigrants does proceed rapidly and inexorably a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(76 citation statements)
references
References 39 publications
3
65
0
8
Order By: Relevance
“…For example, assimilation is reported to be related to early or risky sexual behavior (Harris 1999;Landale and Hauan 1996;Upchurch et al 2001) and higher risks of delinquency and substance abuse (Harris 1999;Nagasawa et al 2001;Zhou and Bankston 1998). Rumbaut (1997) also cites prior research showing detrimental effects of assimilation on adolescents' educational outcomes. However, the effects of assimilation are not always found to be negative -for example, Rhee et al (2003) found acculturation to be related to higher self-esteem for Asian American adolescents.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, assimilation is reported to be related to early or risky sexual behavior (Harris 1999;Landale and Hauan 1996;Upchurch et al 2001) and higher risks of delinquency and substance abuse (Harris 1999;Nagasawa et al 2001;Zhou and Bankston 1998). Rumbaut (1997) also cites prior research showing detrimental effects of assimilation on adolescents' educational outcomes. However, the effects of assimilation are not always found to be negative -for example, Rhee et al (2003) found acculturation to be related to higher self-esteem for Asian American adolescents.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, researchers have suggested that the high motivation levels and achievement-related cultural values of many immigrant groups may spur immigrant children to greater educational accomplishments than their native counterparts. Indeed, empirical research has repeatedly shown that many immigrant children have significantly better educational outcomes than would be predicted on the basis of their family's socioeconomic status (Rumbaut 1997). While some of the variation in outcomes among immigrant children is attributable to systematic differences by national origin, there is still considerable heterogeneity within ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…While there is considerable debate around concepts of assimilation and integration (Alba and Nee 1997;Brubaker 2001;Rumbaut 1997), whether in relation to structural or cultural domains, Berry's four-way categorisation provides us with a widely accepted nomenclature for describing particular intersections on the two axes of ethnic and national identity. Much of the discussion around assimilation has been concerned either with distinguishing its normative from its descriptive aspects (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Brubaker 2001) or assessing whether its predictions do indeed materialise (e.g. Rumbaut 1997). In this paper we use the term assimilation descriptively to define those for whom British national identity predominates.…”
Section: Introductionmentioning
confidence: 99%
“…'Segmented assimilation' processes -i.e., adaptations that take place within varying opportunity structures and are shaped through differential associations, reference groups, experiences, and attachments, especially in primary social relationships stratified by race, religion, region, and class -are not new in the American experience (Rumbaut, 1997). Caste restrictions based on race (extending to all aspects of social life, including citizenship), the 'triple melting pot' of religionbounded intermarriages, the structural pluralism of 'ethclasses,' the persistence of ethnic groups as political interest groups, are all indicative of such adaptations.…”
Section: Contemporary Realities: Prospects and Paradoxesmentioning
confidence: 99%